Study on the drug resistance and pathogenicity of Escherichia coli isolated from calf diarrhea and the distribution of virulence genes and antimicrobial resistance genes - Jia, Yan; Mao, Wei; Liu, Bo; Zhang, Shuangyi; Cao, Jinshan; Xu, Xiaojing (Frontiers in Microbiology, 2022)
The unscientific and irrational use of antimicrobial drugs in dairy farms has led to the emergence of more serious drug resistance in Escherichia coli. In this study, cases of calf diarrhea in cattle farms around the Hohhot area were studied, and Escherichia coli were identified by PCR and biochemical methods, while the distribution of virulence and drug resistance genes of the isolates was analyzed. The results showed that 21 strains of Escherichia coli were isolated from the diseased materials, and the isolation rate was 60%. The isolated strains belong to 15 ST types. The drug resistance levels of the isolated strains to 20 kinds of antimicrobial agent viz., penicillin, ampicillin, cefotaxime, cefepime, cefoxitin, and ceftriaxone were more than 50%. The resistance rate to meropenem was 10%. The resistance rates to tetracycline and doxycycline were 33% and 29%, to ciprofloxacin, levofloxacin and enrofloxacin were 48%, 33%, and 33%, to amikacin, kanamycin and gentamicin were 19%, 24% and 38%, to cotrimoxazole and erythromycin were 48% and 15%, to florfenicol, chloramphenicol and polymyxin B were 29%, 33%, and 5%. Nine strains of pathogenic calf diarrhea Escherichia coli were isolated by mouse pathogenicity test. The detection rates of virulence genes for the adhesion class were fimC (95%), IuxS (95%), eaeA (76%), fimA (62%), ompA (52%) and flu (24%). The detection rates for iron transporter protein like virulence genes were iroN (33%), iutA (19%), fyuA (14%), irp5 (9.5%), Iss (9.5%), and iucD (9.5%). The detection rates for toxin-like virulence genes were phoA (90%), Ecs3703 (57%), ropS (33%), hlyF (14%) and F17 (9.5%). The detection rates of tetracycline resistance genes in isolated strains were tetB (29%), tetA (19%) and tetD (14%). The detection rates for fluoroquinolone resistance genes were parC (Y305H, P333S, R355G) (9.5%), gyrA (S83L, D87N) (28%), qnrD (43%) and qnrS (9.5%). The detection rates for β-lactam resistance genes were blaCTX-M (29%), blaTEM (29%) and blaSHV (9.5%). The detection rates for aminoglycoside resistance genes were strA-B (57%), aacC (33%), aac(3')-IIa (29%) and aadAI (24%). The detection rates of chloramphenicol resistance genes floR and sulfa resistance genes sul2 were 24% and 33%.